2013
DOI: 10.12659/pjr.889613
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of a vein of Galen aneurysmal malformation with MR imaging – report of two cases

Abstract: SummaryBackgroundVein of Galen malformations (VGMs) are rare congenital defects of cerebral vessels. They are formed between the 6th and 11th week of gestation. The background of this defect involves presence of one or more arterovenous fistulas directing bloodflow toward a persistent, dilated, proximal part of median prosencephalic vein (MProsV). Ultrasound examination is a basic test for diagnosis of VGMs. It has now become possible to acquire images of diagnostic value using magnetic resonance (MR) techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Color Doppler ultrasonography is the most often used modality for exploring the fetus . Fetal MRI has become superior to color Doppler ultrasonography in the diagnosis of VGAM in recent years . It was easier to observe the VGAM artery blood supply and affected veins on SSTSE images (black blood sequences).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Color Doppler ultrasonography is the most often used modality for exploring the fetus . Fetal MRI has become superior to color Doppler ultrasonography in the diagnosis of VGAM in recent years . It was easier to observe the VGAM artery blood supply and affected veins on SSTSE images (black blood sequences).…”
Section: Discussionmentioning
confidence: 99%
“…4 Fetal MRI has become superior to color Doppler ultrasonography in the diagnosis of VGAM in recent years. 5 It was easier to observe the VGAM artery blood supply and affected veins on SSTSE images (black blood sequences). In addition, SSFP imaging (white blood sequence) permits the cardiac chambers and vessels to be clearly imaged.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal MRI is now the preferred modality for diagnosing fetal central nervous system (CNS) abnormalities because of its advantages over ultrasonography[ 2 , 27 , 28 ]. Prenatal MRI and MR angiography can identify the prognostic factors (cardiac failure, polyhydramnios, pericardial and pleural effusion, ascites, fetal hydrops, and brain injury) that affect prenatal counseling and aid in delineating the blood supply to the lesion for planning postnatal management[ 2 , 27 - 29 ]. Yuval et al[ 15 ], while enumerating the prognostic features for VGAMs have suggested that neonates with cardiomegaly, dilated vena cava or jugular vein, retrograde aortic flow and multiple feeder arteries may have a better prognosis if there is immediate intervention.…”
Section: Discussionmentioning
confidence: 99%
“…When the fetus matures, the sulci appear ( 27 ). Precise timing of each sulcus is available on atlases, which are used for proper interpretation of fetal brain development ( 12 , 27 , 37 ). An abnormal sulcation pattern may be recognized as numerous sulci that are not expected for a less mature fetus (polymicrogyria) or extremely few sulci (lissencephaly) and cleavage in gray matter extending from the ventricular margin to the brain surface (schizencephaly) in a more mature fetus.…”
Section: Discussionmentioning
confidence: 99%